Frequency of different Histological findings in Patients Undergoing Appendicectomy - Farhan Shahzad, Muhammad Azam Arif, Adeel Ali Tahir, Mr Amir Siddiqui, Muhammad Yasir Naseem, (Pakistan Journal of Medical & Health Sciences, 2022)
Appendectomy remains the most frequently performed emergency abdominal surgical procedure.1,2 The lifetime risk of acute appendicitis for men and women is 8.6% and 6.7%, respectively. Diagnosis of acute appendicitis is made primarily on the basis of the history and the clinical examination. However, histopathologic studies help in diagnosis of acute appendicitis.3 Approximately 20% of patients, those undergoing appendectomy are found not to have acute appendicitis at surgery,86.3% specimens revealed findings of acute appendicitis, 10.8% were normal, while 3% has tuberculosis, 1.5% had Meckle diverticulitis and 0.6% each of adenocarcinoma and Carcinoid tumour. The rationale of study is to find out the burden of different histological findings especially tuberculosis in appendix specimen and compare them with international data. Objective: The objective of this study was to determine the frequency if acute appendicitis, normal appendix and tuberculosis in patients undergoing appendectomy based on histological findings. Study Design: Randomised Control trial (RCT). Setting: Holy Family Hospital Rawalpindi in Surgical Unit-I. Six months, from August 2009 to January 2010. Methods: 98 patients who present in emergency department with signs and symptoms of acute appendicitis were randomly allocated into two groups for open (OA) and laproscopic appendectomy (LA). Data on these two groups was collected and analyzed for operative time and postoperative pain. Results: 98 patients were included in he study (49 patients in each group).Out of 98 there were 37 male and 61 female, respectively. In OA group 18% were male patients and 31% female patients. However in LA group, 19% were male and 30% female patients. The mean age in OA group is 20.18+7.56, and in LA group is 22.24+6.96.The mean operative time in OA group is 33.84 +13.20 in LA group is 37.67+ 11.07.Postoperative pain assessed after 4hours in both groups (visual analogue scale),patients in LA group experienced less postoperative as compare to OA group. Mean VAS in OA group is 7.08 +1.93 in LA group is 3.84+ 1.84 which is statistically significant(p<0.05). Conclusion: Laparoscopic appendectomy is better than open appendectomy for treatment of acute appendicitis in terms of post-operative pain but operative time is same in both of the approaches.